Legitimacy: the missing link in investigating the dynamics of entrepreneurial teams in successful champagne houses. (2017) - Castellano, Sylvaine; Khelladi, Insaf
While recent studies have emphasised the growing interest in entrepreneurial teams, a consensus regarding the benefits of entrepreneurial teams for newly created firms remains lacking. Consequently, legitimacy might represent the missing link in investigating entrepreneurial team dynamics. Legitimacy has been widely used in entrepreneurship research, although never in an entrepreneurial team context. The aim of this article is two-fold: 1) to examine the legitimating role of entrepreneurial teams within successful firms; 2) to investigate the different types of teams in the context of champagne houses. We examine six champagne houses and identify 23 entrepreneurial teams operating in them since their inception. We find that the size, composition and profile of the entrepreneurial team provide different types of legitimacy to champagne houses. This research provides an insightful contribution to the literature on entrepreneurial teams and legitimacy. In the wine context, it also highlights the role of such teams over time.